The Effect of Attention to Self-Regulation of Speech Sound Productions on Speech Fluency in Oral Reading - (:unkn) unknown (My University, 2019)
Purpose: This study ultimately sought to test whether a condition of heightened attention to speech sound production during connected speech serves to trigger increased disfluencies. Disfluencies, or disruptions in the flow of speech, are highly variable in form and location, both within and across individuals and situations. Research to identify conditions that can predictably trigger disfluencies has the potential to provide insight into their elusive nature. A review of related literature covered the cognitive-linguistic theories related to speech fluency and stuttering. This review of previous literature also served as the foundation for why it was proposed that disfluencies would be triggered by heightened self-monitoring attention to how speech sounds are made during connected speech. Methods: Participants included 10 male and 10 female normally fluent adult college students. Their tasks included a baseline oral reading of a 330-word passage, learning of two new speech sounds, followed by an experimental reading of the same passage again. During the experimental reading, target sounds, which were indicated by highlighted locations within the passage, had to be replaced with the newly learned speech sounds. Participants indicated much greater attention was given to how speech sounds were produced during the experimental oral reading than in the baseline oral reading, to support and validate the nature of the task. Results: Disfluencies and oral reading rates were examined using descriptive statistics and analyzed by means of the negative binomial distribution model. Secondary analyses of oral reading rates were conducted with the Wilcoxon’s Signed Rank test. The results revealed that the experimental reading task was associated with a significant increase in Stuttering-Like Disfluency (SLD) and Other Disfluency (OD), and a significant decrease in oral reading rate. Furthermore, SLDs increased significantly more than ODs from the first to the second reading. Discussion: Results supported the hypothesis that disfluency, especially SLD, can be triggered by a condition of increased attention to self-monitoring how speech sounds are produced during connected speech. These findings support theories explaining disfluencies as a symptom of a speaker’s cognitive-linguistic speech planning processes being over-burdened. Implications are raised for specific populations that may be at risk-for more disfluencies: young children learning language, second-language learners, and children in speech therapy. Future research directions are recommended to better understand how to prevent disfluencies in at-risk populations and clarify the enigmatic relationship among attentional processes, phonological production planning, and stuttering.
Keywords: Adults; Attention; Fluency; Oral Reading; Speech; Stuttering